Biogenic fabrication of gold nanoparticles for treatment of gastric cancer and electrochemical sensing of As(lIl) - Ziming Wu; Xbing Shen; Ybao Liu; Mchuan Shi; Jie Li; Zhengyu Zhang (Alexandria Engineering Journal, 2024)
Through the clinical epidemiological observation of gastric cancer, the potential anti-cancer efficacy of the biosynthesized gold nanoparticles (Au-NPs) against the SNU-16 human cancer cell line was studied in details. The MTT investigations on cell viability confirmed the cytotoxic properties of the green formed Au-NPs versus gastric cancer in humans. Propolis was utilized in the synthesis of Au-NPs through an effective biogenic technique in the study. The physiochemical characters of prepared NPs were examined using TEM, UV-Vis spectroscopy and XRD instruments. The electrochemical As(III) sensing capability of the Au-NPs was also investigated with the modification of a screen printed carbon electrode (SPCE). The measuring of As(III) was conducted using the differential pulse voltammetry (DPV) method under closed-circuit mode. A sensitive response for As(III) ions in the concentration range of 0.7 to 60 ppb was acquired using the designed sensor. The modified SPCE was applicable for detection of As(III) in mineral water, tap water and rice flour samples. The achieved results confirm that the biosynthesized Au-NPs pretreated in this research have potential to be employed for electrochemical sensing of toxic heavy metal ions. Moreover, the finding results provide a novel evidence-based medical approach for the prevention and treatment of cancer.